2014
DOI: 10.1007/s11096-014-9944-7
|View full text |Cite
|
Sign up to set email alerts
|

Provision of smoking cessation services in Australian community pharmacies: a simulated patient study

Abstract: Whilst pharmacists' counselling about smoking cessation aids seems satisfactory, further education is required to improve practice standards in terms of matching a patient's history and smoking status to an appropriate product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…We observed that the attitude towards pharmacist-led smoking cessation services was generally positive as the majority (68.5%) were willing to provide these services in their pharmaceutical practice even though their knowledge of specific tobacco cessation strategies and medication appeared to be somewhat limited, as suggested by the quantitative survey and supported by the FGD findings. This is consistent with findings reported among pharmacists in Cracow, Sudan, Australia and Indonesia, which also showed that community pharmacists were willing to provide smoking cessation services even though some of them had limited knowledge 15,16,18,26 .…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the attitude towards pharmacist-led smoking cessation services was generally positive as the majority (68.5%) were willing to provide these services in their pharmaceutical practice even though their knowledge of specific tobacco cessation strategies and medication appeared to be somewhat limited, as suggested by the quantitative survey and supported by the FGD findings. This is consistent with findings reported among pharmacists in Cracow, Sudan, Australia and Indonesia, which also showed that community pharmacists were willing to provide smoking cessation services even though some of them had limited knowledge 15,16,18,26 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to a Saudi Arabian study [ 64 ], the time proved to be a significant influencing factor on the appropriate outcome even though the type of outcome between the two studies is not comparable (UPA dispensed vs. antibiotics dispensed without a prescription). This creates a need for further research about the possible reasons, especially as the best counselling was provided not in the morning as expected on the basis of the model of the performance curve [ 82 ] but instead from midday to the late afternoon.…”
Section: Discussioncontrasting
confidence: 84%
“…Out of the 1107 papers in the original search and two added due to quoting the 2006 review, 148 papers met the criteria . Extraction of relevant papers from those found by the search strategy was done jointly by two researchers (IB and PN) and independently by a third researcher (AA).…”
Section: Resultsmentioning
confidence: 99%